Teaching Material Development Practical Guidelines For Reading Al-Qur’an in Learning Al-Qur’an at Griya Al-Qur’an of Surabaya - Khoirul Huda; Mahsun Jayadi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
The manuscripts of Qur'an that are scattered around us are divided into 2 types i.e. Indonesian standard manuscripts and the Middle East or Madinah standard, the development of these two manuscripts is not balanced with the refining of teaching materials or the Qur'anic learning method, 90% of the methods refer to Indonesian standard manuscripts and the rest refer to Mushaf Madinah. This challenge was answered by the Griya Al-Qur’an to provide a method that refers to the Mushaf Madinah which has been running for 7 years and has printed 14,000 books that should have been revised as soon as the input from the user (asatizah). The three problems became the study of this thesis. First, how to describe the learning of the Qur'an? Second, how to develop teaching material? And third what is the effectiveness of teaching materials?. This study used an R & D approach or in practice mixed between qualitative and quantitative, qualitative to measure the depth of the material as well as quantitatively to measure validity and effectiveness of teaching materials. The results of the study were as follows: First, the Qur'an Learning should pay attention to 7 components of learning namely goals, material, students, teachers, methods, tools and assessment systems. Second, to develope this teaching material, the ADDIE stage was analyzed, the results of which were revised focus on adding volume 1 and changing the paper size, designed by making a re-design of the material based on the analysis results and preparing the Mushaf Madinah printing software with the Usmani hafs V09 font, Development by implementing what has been designed and invited material experts and instructional media experts to test validity with the results of the experts' values of 80% and 76%, respectively, which meant valid. The third was to measure effectiveness through the implementation stage by conducting a trial with the pretest result of 33% and posttest of 79% which meant that this teaching material was effective and ended with evaluation by evaluating each stage of development. Keywords: Teaching materias Development , Griya Al-Qur’an, Qur'an Learning